STIRRED FLUIDIZED-BED DRYER OF REGENERATED ION EXCHANGER PARTICLES - Michal Pěnička; Pavel Hoffman; Ivan Fořt (Acta Polytechnica, 2014)
This article describes intensification of the fluidized-bed drying process for regenerated spherical-shape ion exchanger particles in the batch mode, achieved by a mechanical stirrer in the fluidized bed layer of the dried particles. The effect of the mechanical stirring system on the drying process was examined. Calculations as well as results of comparison measurements provide evidence of a favourable effect of stirring on the total drying time as compared to the initial unstirred system. The regenerated ion exchanger particles pass to the fluid state in a shorter time and the ultimate total drying time is thus more than 60% shorter.